2002
DOI: 10.1046/j.1525-1497.2002.10522.x
|View full text |Cite
|
Sign up to set email alerts
|

The limited incorporation of economic analyses in clinical practice guidelines

Abstract: BACKGROUND: Because there is increasing concern that economic data are not used in the clinical guideline development process, our objective was to evaluate the extent to which economic analyses are incorporated in guideline development. METHODS: We searched medline and HealthSTAR databases to identify English‐language clinical practice guidelines (1996–1999) and economic analyses (1990–1998). Additional guidelines were obtained from The National Guidelines Clearinghouse Internet site available at http://www.g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 151 publications
0
13
0
Order By: Relevance
“…While information from cost-effectiveness studies is rarely formally integrated into guideline development (25), given the reality of finite health care resources, it is imperative to explicitly integrate findings from such analyses into recommendations to ensure health system sustainability. Relying on drug acquisition costs alone may not be reliable to estimate cost effectiveness, particularly in jurisdictions where the relative differences among drug class costs have decreased.…”
Section: Acei Angiotensin-converting Enzyme Inhibitors; Arb Angiotensmentioning
confidence: 99%
“…While information from cost-effectiveness studies is rarely formally integrated into guideline development (25), given the reality of finite health care resources, it is imperative to explicitly integrate findings from such analyses into recommendations to ensure health system sustainability. Relying on drug acquisition costs alone may not be reliable to estimate cost effectiveness, particularly in jurisdictions where the relative differences among drug class costs have decreased.…”
Section: Acei Angiotensin-converting Enzyme Inhibitors; Arb Angiotensmentioning
confidence: 99%
“…Only 41.6% made any mention of projected effects on health care costs, and only 14.3% quantified these estimates in any way. A 2002 study on the incorporation of published cost-effectiveness analysis in published clinical guidelines showed that, using guidelines as the unit of analysis, 9 of 35 (26%) incorporated at least 1 economic analysis of above-average quality in the text and 11 of 35 (31%) incorporated at least 1 in the references [8]. Finally, a search of the database of the National Guideline Clearinghouse [9] showed that of 1616 guidelines published between 2000–2005, only 369 or 23% had a formal cost analysis.…”
Section: What Other Organizations Are Doing?mentioning
confidence: 99%
“…Several experts advocate the use of weighted items of checklists for the evaluation of economic analyses (Ungar and Santos 2003;Gonzalez Perez 2002). Moreover, currently available scoring systems for assessing the quality of economic analysis are, in same cases, not based on a well-known and commonly shared checklist but on key elements drawn from different checklists (Chiou 2003;Wallace 2002;Ungar and Santos 2003); others were developed which gave a full score to items for which an explicit answer was retrievable in the text and half score in the case of a not clear answer in the text (Gonzalez Perez 2002). All these systems were judged to be useful for researchers and policy-makers to evaluate the quality of studies, even though they have limits.…”
Section: Introductionmentioning
confidence: 99%